A chemogenomic approach is required for effective treatment of amyotrophic lateral sclerosis - Georgios Pampalakis; Georgios Angelis; Eleni Zingkou; Kostas Vekrellis; Georgia Sotiropoulou (Clinical and Translational Medicine, 2022)
Abstract ALS is a fatal untreatable disease involving degeneration of motor neurons. Μultiple causative genes encoding proteins with versatile functions have been identified indicating that diverse biological pathways lead to ALS. Chemical entities still represent a promising choice to delay ALS progression, attenuate symptoms and/or increase life expectancy, but also gene‐based and stem cell‐based therapies are in the process of development, and some are tested in clinical trials. Various compounds proved effective in transgenic models overexpressing distinct ALS causative genes unfortunately though, they showed no efficacy in clinical trials. Notably, while animal models provide a uniform genetic background for preclinical testing, ALS patients are not stratified, and the distinct genetic forms of ALS are treated as one group, which could explain the observed discrepancies between treating genetically homogeneous mice and quite heterogeneous patient cohorts. We suggest that chemical entity‐genotype correlation should be exploited to guide patient stratification for pharmacotherapy, that is administered drugs should be selected based on the ALS genetic background.